Halitosis among users of electronic nicotine delivery systems in a multi-center cross-sectional study - Saadi M. Saleh; Abdelrahman Shata; Ali Malik Tiryag; Bishoy G. Malak; Ahmad M. A. Okour; Maher A. Atiyah; Wisam Al-Khaboori; Mahmoud Raslan; Abanob A. Helmy; Ata Al-howaity; Rana Nasser Saeed; Menna M. Aboelkhier; et al. (Scientific Reports, 2025)
Abstract The global utilization of Electronic Nicotine Delivery Systems (ENDS) is increasing, with emerging evidence suggesting a potential link between ENDS and halitosis. Nonetheless, direct data addressing this association remains limited. This study aimed to investigate the effects of ENDS usage on halitosis among individuals aged 18–40 in 18 Middle Eastern and North African (MENA) countries. The study was conducted between November 2023 and May 2024, and employed an online self-administered survey that included the validated Halitosis Finding Score (Halfins). The analysis included a total of 7,973 participants categorized by their smoking habits: 71.1% identified as non-users, 12.6% as ENDS users, 10.8% as traditional tobacco users, and 5.5% as dual users. After adjusting for potential confounders, exclusive ENDS users exhibited significantly greater odds of experiencing halitosis (adjusted odds ratio [AOR] = 1.576, 95% CI = 1.367–1.817, p < 0.001), as did dual users (AOR = 1.420, 95% CI = 1.161–1.738, p < 0.001), than non-users did. These findings suggest that the use of ENDS and dual usage may elevate the risk of developing halitosis. However, due to the limitations of the study, it is important to interpret these results with caution. Nonetheless, reducing the use of ENDS could potentially mitigate the risk of halitosis.